Improvement of feed resources and livestock feeding in mixed cropping systems - Blümmel, Michael; Anandan, S.; Wright, Iain A. (Satish Serial Publishing House, 2012)
The rapid changes in the scientific know how of the science of animal nutrition have taken place in last two decades. There is a much felt need for a text book of advanced animal nutrition for students form Asian and other developing countries. This book is written in a very simple illustrative and coherent manner with all updated information so that students, scientists/researchers and academicians, at national and international level will be benefited. This book is the result of a multi-author effort. The contributors were invited at national as well as international level for their expertise as topics and professional involvement. This book attempts at providing a clear, thorough and up-dated information fundamentals to animal nutrition, as well as its application, each topic is discussed form a multidisciplinary angle to aid and assist understanding, and not merely as a routine to fulfill the requirement of syllabi. Many chapters are devoted to special topics in changing scenario of animal nutrition, some recent topics like global warming due to methane emission by livestock, environmental issues in livestock rearing and polices, quality assurance for livestock production and prospects of feed from generically modified plants in livestock feeding etc. have been introduced. In editors opinion this book will be extremely useful to all persons at national and international level who are directly involved with the science of animal nutrition.